1998
DOI: 10.1002/(sici)1521-3765(19981102)4:11<2117::aid-chem2117>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Reactivity, and Ring-Opening Polymerization (ROP) of Tin-Bridged [1]Ferrocenophanes

Abstract: Abstract:The first examples of tinbridged [1]ferrocenophanes, Fe(h-C 5 H 4 ) 2 -SntBu 2 (7a) and Fe(h-C 5 H 4 ) 2 SnMes 2 (7b) have been synthesized by the low-temperature reaction of Fe(h-C 5 H 4 Li) 2´n TME-DA (TMEDA N,N,N',N'-tetramethylethylenediamine) with tBu 2 SnCl 2 and Mes 2 SnCl 2 (Mes 2,4,6-trimethylphenyl), respectively. They were isolated in 65 % (7a) and 85% (7b) yield as orange crystalline solids, which were characterized by multinuclear NMR and UV/Vis spectroscopy, mass spectrometry, elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 16 publications
9
112
1
2
Order By: Relevance
“…They show at least one reversible oxidation wave, however, at surprisingly high anodic potentials, making formation of such complexes difficult. Tin- [1]ferrocenophanes [69,70] reveal again reversible one-electron signals in CV with E 0 close to that of the parent ferrocene, while (dimethylsilylen)-[1]ferrocenophane appears to become chemically irreversible under comparable conditions [70]. Selena-and thia- [1]ferrocenophanes are also known [71] and show similar behavior as regards reversibility.…”
Section: Metallocenophanes and Metallametallocenophanesmentioning
confidence: 99%
“…They show at least one reversible oxidation wave, however, at surprisingly high anodic potentials, making formation of such complexes difficult. Tin- [1]ferrocenophanes [69,70] reveal again reversible one-electron signals in CV with E 0 close to that of the parent ferrocene, while (dimethylsilylen)-[1]ferrocenophane appears to become chemically irreversible under comparable conditions [70]. Selena-and thia- [1]ferrocenophanes are also known [71] and show similar behavior as regards reversibility.…”
Section: Metallocenophanes and Metallametallocenophanesmentioning
confidence: 99%
“…[175][176][177][178] The ROP of ferrocenophanes with tin bridges has also been described by the research groups of Manners and Pannell. [179][180][181][182] It was reported that high-molecularweight polymers could be produced by thermal ROP, and that the ferrocenophanes also opened at room temperature in solution. [179][180][181] It was also discovered that the ringopening of tin-bridged [1]ferrocenophanes in solution is accelerated by the addition of amines.…”
Section: Ring-opening Polymerizationmentioning
confidence: 99%
“…[179][180][181][182] It was reported that high-molecularweight polymers could be produced by thermal ROP, and that the ferrocenophanes also opened at room temperature in solution. [179][180][181] It was also discovered that the ringopening of tin-bridged [1]ferrocenophanes in solution is accelerated by the addition of amines. [181] The same observation was noted upon the addition of pyridine to solutions of ferrocenophanes containing silicon and germanium bridges as shown in Scheme 48, however, the siliconcontaining monomer displayed much lower reactivity than the other monomers.…”
Section: Ring-opening Polymerizationmentioning
confidence: 99%
“…24 Comparisons of the behavior of PFSs with that of other polyferrocenes indicate that the metal-metal interactions are influenced by the silicon spacer. 27 A recent analysis discusses the influence of the spacer on the molecular scale dielectric constant of the medium between the iron centers that mediates the interactions detected. According to this approach, the presence of more polarizable atoms (e.g., Si vs C) would be expected to lead to an increased Fe•••Fe interaction, which is indeed observed.…”
Section: Properties Of Ring-opened Polyferrocenes: Pfssmentioning
confidence: 99%
“…However, polyferrocenylethylenes 9 (M ϭ Fe, E ϭ EЈ ϭ CH 2 , RЈ ϭ Me) with a CH 2 OCH 2 spacer (and other polymers derived from the ROP of [2]ferrocenophanes) possess much weaker metal-metal interactions than PFSs, whereas for polyferrocenylsulfides 7 (E ϭ S) the interaction is stronger. 27,37 Polyferrocenylphosphines (PFPs) 7 (E ϭ PR) offer additional possibilities because facile coordination of transition metals to phosphorus is possible. distribution is broad (PDI ϭ ca.…”
Section: Properties Of Ring-opened Polyferrocenes: Pfssmentioning
confidence: 99%